Silenced by performativity: The child’s right to a spiritual voice in an age of neoliberal educational imperatives - Hyde, Brendan (International journal of children's spirituality, 2021)
This paper argues the importance of maintaining and promoting the child’s spiritual voice in spite of educational practices that have been reformed to align with the neoliberal agenda, in particular, performativity. Descriptions of spirituality are offered, noting that spirituality is a part of human life that emerges in childhood, and a case made for the necessity of the child’s spiritual voice in the light of the United Nations Convention on the Rights of the Child. The neoliberal discourse of performativity in education is discussed, and ways this may serve to silence the spiritual voice of the child are indicated. While acknowledging that further research is necessary, the notion of rights-respecting curriculum is posited as a way of nurturing and promoting the child’s spiritual voice in education.